Contribution of grain boundary to strength and electrical conductivity of annealed copper wires - Liming Dong; Fei Yang; Tianbo Yu; Ning Zhang; Xuefeng Zhou; Zonghan Xie; Feng Fang (Journal of Materials Research and Technology, 2023)
The effect of grain boundaries on the strength and electrical conductivity of annealed copper wires was studied. After annealing at 100 °C for 30 min, the copper wires retained a fiber-like structure. The increase in electrical conductivity is believed to stem from the decrease of crystallographic defects introduced by drawing. Recrystallization occurred when the annealing temperature reached 150 °C. The formation of small recrystallized grains led to the introduction of additional grain boundaries perpendicular to the drawing direction, resulting in a slight decrease in electrical conductivity. When the annealing temperature rose up to 200 °C, complete recrystallization took place in the copper wires. The grain boundaries parallel to the drawing direction play an important role in boundary strengthening, while the grain boundaries perpendicular to the drawing direction play an important role in both boundary strengthening and electron scattering. The electrical resistivity of grain boundaries in fully recrystallized copper wires at room temperature was determined experimentally, and an empirical relation is proposed to quickly determine the electric conductivity of copper wires at room temperature based on the boundary spacing along the drawing direction.